HUBUNGAN BESI DAN PRODUKSI SITOKIN - Suega, Ketut (journal of internal medicine; Vol. 7, No. 2 Mei 2006, 2012)
Iron deficiency is a widespread nutritional disorder in infant, children and women of reproductive age especially in developing countries where almost 2 billion individuals are concerned, particularly infant and children. The absorption of intestinal iron as regulated in several ways such as dietary regulator, stores regulator and erythropoietic regulator. The negative consequence iron deficiency anemia on behavior, psychomotor development and growth rate are well established and underlined the need to control iron deficiency anemia. Iron supplementation has proven to be useful, particularly in infant and children, when iron deficiency is important and has to be corrected rapidly. However several studies have indicated that iron deficiency protects against infection and other studies show the opposite where morbidity is higher in iron deficient children. Iron deficiency would decrease the resistance to infection through impairment of immune competence of the individual especially cell-mediated immunity. The mechanisms of impairment are very likely multifactorial and may include but not be limited to a reduction in the activity of certain iron-dependent enzymes such as ribonucleated reductase. Other mechanism may include a defect in one or several of the early events of lymphocyte activation and cytokine productions such as IL-2. The main cellular source of IL-2 is activated lymphocyte and TCR/CD3 actvation leads to autocrine IL-2/high affinity receptor signal transduction, resulting in cell proliferation. Iron deficiency may inactivated T cell proliferation and decreasing IL-2 production.
Keywords: iron deficiency, cytokine production, IL-2